Security strategies, power disparity and identity : the Baltic Sea region - Knudsen, Olav (2007)
An overall perspective on regional power strategies / Olav F. Knudsen – Power disparities and the avoidance of confrontation / Olav F. Knudsen – Events and ideas in the region : an overview 1980s-2000s / Olav F. Knudsen and Christopher Jones – The conditionality of security integration : identity and alignment choices in Finland and Sweden / Regina Karp – Power disparity and epistemic communities : the Paldiski case / Michael Karlsson – Threat images and socialization : Estonia and Russia in the new millennium / Erik Noreen – Power disparity in the digital age / Johan Eriksson – Generalizing about security strategies in the Baltic Sea region / Stephen G. Walker – Looking to the future : security strategies, identity and power disparity / Olav F. Knudsen